Preparation method of single crystal black silicon suede, TOPCon solar cell and photovoltaic system
By using metal -assisted chemical etching legal system in the silicon solar cell, the deep cylindrical nano -shaped black silicon surface is used, and the alkaline solution is used to etched into the inverted pyramid structure. The lack of effects improves the photoelectric conversion efficiency and opening voltage of solar cells.
Patent Information
- Application Number
- CN202411529955.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-28
Smart Images

Figure CN119384075A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of crystalline silicon solar cells, and in particular to a method for preparing a single-crystal black silicon velvet surface, a TOPCon solar cell and a photovoltaic system. Background Art
[0002] Silicon solar cells are photoelectric conversion devices that use silicon materials as semiconductors and can convert sunlight into electrical energy. Silicon solar cells can be divided into single-crystal silicon, polycrystalline silicon and thin-film silicon solar cells according to the morphology of silicon materials. At present, the silicon wafers of mainstream silicon solar cells on the market mainly use wet etching to obtain a pyramid-shaped velvet structure. This velvet structure can ensure good light trapping and passivation effects and reduce non-radiative recombination. However, compared with black silicon (b-Si) velvet, the light loss of the pyramid-shaped velvet structure obtained by wet etching is more serious, which will cause part of the current loss, thereby reducing the photoelectric conversion efficiency of silicon solar cells. However, the surface recombination center density of the traditional black silicon (b-Si) velvet structure is high, and it is not easy to obtain a good passivation effect from the subsequent process, resulting in a low open circuit voltage (Voc) of the solar cell, thereby reducing the photoelectric conversion efficiency of the solar cell.
[0003] It should be noted that the above content is not necessarily prior art, nor is it intended to limit the scope of patent protection of this application. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present application is to provide a method for preparing a single-crystal black silicon velvet, a TOPCon solar cell and a photovoltaic system. First, a black silicon (b-Si) nano-velvet structure is prepared based on a metal-assisted chemical etching method (MACE) to form a densely and evenly arranged deep cylindrical nanoporous black silicon velvet; then, an alkaline solution is used to etch and reconstruct the surface velvet, and the shallow surface of the densely arranged deep cylindrical nanopores on the surface of the black silicon (b-Si) nano-velvet structure is etched. Due to the anisotropic etching, the deep nanopores are converted into square pits, and more nanoscale inverted pyramid structures appear at the bottom, the average pore diameter is increased, and the average pore depth is shortened. The reconstructed velvet surface presents a uniform texture, and the surface / volume ratio is greatly reduced, thereby reducing the density of the recombination center, which is conducive to obtaining a good passivation effect in the subsequent process, while also ensuring an excellent light trapping effect, and improving the photoelectric conversion efficiency and open circuit voltage of the solar cell.
[0005] To achieve the above objectives, this application adopts the following technical solutions: A method for preparing a single crystal black silicon velvet surface, comprising: Putting a single crystal silicon wafer into a black silicon texturing solution, and performing metal-assisted chemical etching on the single crystal silicon wafer to form a cylindrical nanoporous black silicon texturing surface, thereby obtaining a target single crystal silicon wafer; Reconstructing the cylindrical nanoporous black silicon texture of the target single crystal silicon wafer by etching with an alkaline solution to form an inverted pyramid texture structure; Among them, the average pore diameter of the cylindrical nanoporous black silicon velvet surface is smaller than the average tower base length of the inverted pyramid velvet surface structure, and the average pore depth of the cylindrical nanoporous black silicon velvet surface is greater than the average tower height of the inverted pyramid velvet surface structure.
[0006] In some embodiments, the pore size of the cylindrical nanoporous black silicon velvet surface is 40 to 80 nm, and the pore depth of the cylindrical nanoporous black silicon velvet surface is 150 to 250 nm; and / or The length of the tower base of the inverted pyramid-shaped velvet structure is 180-220 nm, and the tower height of the inverted pyramid-shaped velvet structure is 100-140 nm.
[0007] In some embodiments, the black silicon texturing solution includes silver nitrate, hydrogen fluoride, hydrogen peroxide, and water; wherein the concentration of the silver nitrate is 0.001-0.003 mol / L, the concentration of the hydrogen fluoride is 8-9 mol / L, and the concentration of the hydrogen peroxide is 0.3-0.6 mol / L.
[0008] In some embodiments, during the metal-assisted chemical etching of the single crystal silicon wafer, the temperature is controlled at 25-30° C. and the time is controlled at 2-4 min.
[0009] In some embodiments, before the target single crystal silicon wafer is subjected to alkaline solution etching reconstruction, the method further includes: sequentially using deionized water, a nitric acid solution with a nitric acid concentration of 0.0008 to 0.0012 mol / L, and deionized water to clean the target single crystal silicon wafer; and / or The target single crystal silicon wafer is placed in a hydrofluoric acid solution having a mass concentration of 1 to 4% of hydrogen fluoride for etching for 30 to 60 seconds.
[0010] In some embodiments, the alkaline solution is at least one of a sodium hydroxide solution and a potassium hydroxide solution.
[0011] In some embodiments, the alkaline solution further comprises n-butanol; the concentration of the alkali in the alkaline solution is 0.4-0.6 mol / L, and the mass concentration of the n-butanol is 5-10%.
[0012] In some embodiments, the method of reconstructing the cylindrical nanoporous black silicon texture of the target single crystal silicon wafer by etching with an alkaline solution comprises: Placing the target single crystal silicon wafer into the alkaline solution for etching and reconstruction for 20 to 30 seconds; or Firstly, the target single crystal silicon wafer is placed in a first alkaline solution for etching and reconstruction for 10 to 15 seconds, and then the target single crystal silicon wafer is placed in a second alkaline solution for etching and reconstruction for 10 to 15 seconds; Wherein, the first alkaline solution is a sodium hydroxide solution, the concentration of sodium hydroxide in the first alkaline solution is 0.4-0.5 mol / L, and the mass concentration of n-butanol is 5-7%; the second alkaline solution is a potassium hydroxide solution, the concentration of potassium hydroxide in the second alkaline solution is 0.55-0.6 mol / L, and the mass concentration of n-butanol is 9-10%.
[0013] The present application also provides a TOPCon solar cell, comprising a single crystal silicon wafer prepared by the above method; The TOPCon solar cell is prepared by the following operations: on the single crystal silicon wafer, a PN junction, a silicon dioxide tunneling layer, an n-doped amorphous silicon film, an aluminum oxide film, a silicon nitride anti-reflection film and a metal electrode are sequentially prepared.
[0014] The present application also provides a photovoltaic system, comprising the above-mentioned TOPCon solar cell.
[0015] In the technical solution of the present application, a black silicon (b-Si) nano-suede structure is first prepared based on a metal-assisted chemical etching method (MACE) to form a densely and evenly arranged deep cylindrical nanoporous black silicon suede; then, an alkaline solution is used to etch and reconstruct the surface suede, and the shallow surface of the densely arranged deep cylindrical nanopores on the surface of the black silicon (b-Si) nano-suede structure is etched. Due to anisotropic etching, the deep nanopores are converted into square pits, and more nanoscale inverted pyramid structures appear at the bottom, the average pore diameter increases, and the average pore depth shortens. The reconstructed suede surface presents a uniform texture, and the surface / volume ratio is greatly reduced, thereby reducing the density of the recombination center, which is conducive to obtaining a good passivation effect in the subsequent process, while also ensuring an excellent light trapping effect, and improving the photoelectric conversion efficiency and open circuit voltage of solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In the accompanying drawings, unless otherwise specified, the same reference numerals throughout the multiple drawings represent the same or similar parts or elements. These drawings are not necessarily drawn to scale. It should be understood that these drawings only depict some embodiments disclosed in the present application and should not be regarded as limiting the scope of the present application. Figure 1 This is a schematic diagram of the surface structure of a single crystal silicon wafer before and after metal-assisted chemical etching in an embodiment of the present application.
[0017] Figure 2 This is a schematic diagram of the surface structure of a single crystal silicon wafer before and after alkaline solution etching and reconstruction in an embodiment of the present application. DETAILED DESCRIPTION
[0018] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. In the accompanying drawings, for clarity, the sizes of layers, regions, elements and their relative sizes may be exaggerated. Wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limitations on the present application. It should be noted that, in the absence of conflict, the embodiments in the present application and the features in the embodiments can be combined with each other.
[0019] It should be understood that when an element or layer is referred to as "on ...", "adjacent to ...", "connected to" or "coupled to" other elements or layers, it can be directly on, adjacent to, connected to or coupled to other elements or layers, or there can be intervening elements or layers. On the contrary, when an element is referred to as "directly on ...", "directly adjacent to ...", "directly connected to" or "directly coupled to" other elements or layers, there is no intervening element or layer. It should be understood that although the terms first, second, third, etc. can be used to describe various elements, components, regions, layers and / or parts, these elements, components, regions, layers and / or parts should not be limited by these terms. These terms are only used to distinguish one element, component, region, layer or part from another element, component, region, layer or part. Therefore, without departing from the teachings of the present disclosure, the first element, component, region, layer or part discussed below can be represented as the second element, component, region, layer or part. And when the second element, component, region, layer or part is discussed, it does not mean that the present disclosure necessarily has the first element, component, region, layer or part.
[0020] In this application, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0021] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those illustrated or described herein, for example. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0022] In the present application, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to an integer in the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints, which is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical range disclosed in the present application should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows for broadly including quantitative intervals such as percentage intervals, ratio intervals, and ratio intervals.
[0023] The embodiment of the present application aims to provide a method for preparing a single-crystal black silicon velvet, a TOPCon solar cell and a photovoltaic system. First, a black silicon (b-Si) nano-velvet structure is prepared based on a metal-assisted chemical etching method (MACE) to form a densely and evenly arranged deep cylindrical nanoporous black silicon velvet; then, an alkaline solution is used to etch and reconstruct the surface velvet, and the shallow surface of the densely arranged deep cylindrical nanopores on the surface of the black silicon (b-Si) nano-velvet structure is etched. Due to anisotropic etching, the deep nanopores are converted into square pits, and more nanoscale inverted pyramid structures appear at the bottom, the average pore diameter is increased, and the average pore depth is shortened. The reconstructed velvet surface presents a uniform texture, and the surface / volume ratio is greatly reduced, thereby reducing the density of the recombination center, which is conducive to obtaining a good passivation effect in the subsequent process, while also ensuring an excellent light trapping effect, and improving the photoelectric conversion efficiency and open circuit voltage of the solar cell. Compared with the positive pyramid velvet structure and the inverted pyramid velvet structure obtained by wet etching, the nanoscale inverted pyramid structure prepared by the method of the embodiment of the present application has better light trapping effect and passivation effect, which can further improve the open circuit voltage (Voc) and photoelectric conversion efficiency of solar cells. Compared with the traditional black silicon (b-Si) velvet structure, the nanoscale inverted pyramid structure prepared by the method of the embodiment of the present application has better passivation effect, which plays a role in further improving the open circuit voltage (Voc) and photoelectric conversion efficiency of solar cells.
[0024] The present application provides a method for preparing a single-crystal black silicon texture, comprising: Putting a single crystal silicon wafer into a black silicon texturing solution, and performing metal-assisted chemical etching on the single crystal silicon wafer to form a cylindrical nanoporous black silicon texturing surface, thereby obtaining a target single crystal silicon wafer; Reconstructing the cylindrical nanoporous black silicon texture of the target single crystal silicon wafer by etching with an alkaline solution to form an inverted pyramid texture structure; Among them, the average pore diameter of the cylindrical nanoporous black silicon velvet surface is smaller than the average tower base length of the inverted pyramid velvet surface structure, and the average pore depth of the cylindrical nanoporous black silicon velvet surface is greater than the average tower height of the inverted pyramid velvet surface structure.
[0025] In the embodiment of the present application, the single crystal silicon wafer can be an N-type single crystal silicon wafer or a P-type single crystal silicon wafer. The black silicon texturing liquid contains silver, copper or nickel, that is, when the single crystal silicon wafer is subjected to metal-assisted chemical etching, the metal catalyst used can be silver, copper or nickel. The composition ratio of the black silicon texturing liquid can be adjusted according to actual needs, and a uniformly distributed cylindrical nanoporous black silicon velvet surface can be formed. In addition, single-sided texturing or double-sided texturing can be selected according to actual needs.
[0026] In the embodiment of the present application, the alkaline solution used for etching and reconstructing the cylindrical nanoporous black silicon velvet surface can be a sodium hydroxide solution, a potassium hydroxide solution, a tetramethylammonium hydroxide solution, a mixed solution of sodium hydroxide and potassium hydroxide, ammonia water or a solution containing ammonia water. The concentration, type, temperature and other parameters of the alkaline solution can be adjusted according to actual needs to facilitate the formation of an inverted pyramid velvet structure. In addition, the size of the inverted pyramid velvet structure formed satisfies: the average pore size of the cylindrical nanoporous black silicon velvet surface is smaller than the average tower bottom side length of the inverted pyramid velvet structure, and the average pore depth of the cylindrical nanoporous black silicon velvet surface is greater than the average tower height of the inverted pyramid velvet structure; that is, the velvet structure formed by etching and reconstruction meets the conditions of increasing the average pore size, shortening the average pore depth, and reducing the surface / volume ratio, which can reduce the density of the composite center, which is conducive to obtaining a good passivation effect from the subsequent process, while also ensuring an excellent light trapping effect.
[0027] In the embodiment of the present application, a black silicon (b-Si) nano-suede structure is first prepared based on a metal-assisted chemical etching method (MACE) to form a densely and evenly arranged deep cylindrical nanoporous black silicon suede; then an alkaline solution is used to etch and reconstruct the surface suede, and the shallow surface of the densely arranged deep cylindrical nanopores on the surface of the black silicon (b-Si) nano-suede structure is etched. Due to the anisotropic etching, the deep nanopores are converted into square pits, and more nanoscale inverted pyramid structures appear at the bottom, the average pore diameter is increased, and the average pore depth is shortened. The reconstructed suede surface presents a uniform texture, and the surface / volume ratio is greatly reduced, thereby reducing the density of the recombination center, which is conducive to obtaining a good passivation effect in the subsequent process, while also ensuring an excellent light trapping effect, and improving the photoelectric conversion efficiency and open circuit voltage of the solar cell.
[0028] In an optional embodiment, the pore size of the cylindrical nanoporous black silicon velvet surface is 40 to 80 nm (for example, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm), and the pore depth of the cylindrical nanoporous black silicon velvet surface is 150 to 250 nm (for example, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm, 210 nm, 220 nm, 230 nm, 240 nm, 250 nm); and / or The bottom side length of the inverted pyramid shaped velvet structure is 180-220 nm (for example, 180 nm, 190 nm, 200 nm, 210 nm, 220 nm), and the height of the inverted pyramid shaped velvet structure is 100-140 nm (for example, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm).
[0029] In the embodiment of the present application, controlling the size of the cylindrical nanoporous black silicon velvet can, on the one hand, increase the light trapping effect, be beneficial to light capture, reduce light reflection loss, and thus improve the photoelectric conversion efficiency of the battery; on the other hand, controlling the size of the cylindrical nanoporous black silicon velvet is beneficial to the subsequent alkaline solution etching reconstruction step, and the alkaline solution etching reconstruction effect is better. The reconstructed velvet surface presents a more uniform texture, reduces the density of the composite centers, and is conducive to obtaining a good passivation effect in the subsequent process. At the same time, it can also ensure an excellent light trapping effect, thereby further improving the photoelectric conversion efficiency of the battery.
[0030] In an optional embodiment, the black silicon texturing solution includes silver nitrate, hydrogen fluoride, hydrogen peroxide, and water; wherein the concentration of the silver nitrate is 0.001-0.003 mol / L (for example, 0.001 mol / L, 0.002 mol / L, 0.003 mol / L), the concentration of the hydrogen fluoride is 8-9 mol / L (for example, 8 mol / L, 8.2 mol / L, 8.4 mol / L, 8.6 mol / L, 8.8 mol / L, 9 mol / L), and the concentration of the hydrogen peroxide is 0.3-0.6 mol / L (for example, 0.3 mol / L, 0.35 mol / L, 0.4 mol / L, 0.45 mol / L, 0.5 mol / L, 0.55 mol / L, 0.6 mol / L).
[0031] In the embodiment of the present application, silver-assisted chemical etching is used to optimize the composition ratio of the black silicon texturing solution, which can improve the microstructure of the velvet surface and facilitate obtaining a black silicon velvet surface with densely and evenly arranged cylindrical nanopores. On the one hand, it can increase the light trapping effect, which is beneficial to light capture and reduces light reflection losses, thereby improving the photoelectric conversion efficiency of the battery; on the other hand, controlling the microstructure of the cylindrical nanoporous black silicon velvet surface is beneficial to the subsequent alkaline solution etching reconstruction step. The alkaline solution etching reconstruction effect is better, and the reconstructed velvet surface presents a more uniform texture, reducing the density of the composite centers, which is beneficial to obtaining a good passivation effect in the subsequent process, while also ensuring an excellent light trapping effect, thereby further improving the photoelectric conversion efficiency of the battery.
[0032] In an optional embodiment, during the metal-assisted chemical etching of the single crystal silicon wafer, the temperature is controlled at 25-30°C (for example, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C), and the time is controlled at 2-4 minutes (for example, 2 minutes, 2.5 minutes, 3 minutes, 3.5 minutes, 4 minutes).
[0033] In the embodiment of the present application, optimizing the temperature and time of metal-assisted chemical etching can affect the diffusion effect of the etchant, thereby improving the microstructure of the velvet surface, making it easier to obtain a black silicon velvet surface with densely and uniformly arranged cylindrical nanopores, which can increase the light trapping effect, is beneficial to light capture, and reduces light reflection losses, thereby further improving the photoelectric conversion efficiency of the battery.
[0034] In an optional embodiment, before the target single crystal silicon wafer is subjected to alkaline solution etching reconstruction, the process further includes: sequentially using deionized water, a nitric acid solution having a nitric acid concentration of 0.0008 to 0.0012 mol / L (for example, 0.0008 mol / L, 0.0009 mol / L, 0.0010 mol / L, 0.0011 mol / L, 0.0012 mol / L), and deionized water to clean the target single crystal silicon wafer; and / or The target single crystal silicon wafer is placed in a hydrofluoric acid solution having a mass concentration of hydrogen fluoride of 1 to 4% (eg, 1%, 2%, 3%, 4%) and etched for 30 to 60 seconds (eg, 30 seconds, 40 seconds, 50 seconds, 60 seconds).
[0035] In the embodiment of the present application, the purpose of sequentially treating the target single crystal silicon wafer with deionized water, nitric acid solution, and deionized water is to remove metal residues and other residues generated during the metal-assisted chemical etching process. The purpose of treating the target single crystal silicon wafer with hydrofluoric acid solution is to clean the silicon oxide layer grown during the metal-assisted chemical etching process. After the metal-assisted chemical etching, before the alkaline solution etching reconstruction, the target single crystal silicon wafer is subjected to impurity removal treatment, and the alkaline solution etching reconstruction effect is better. The reconstructed velvet surface presents a more uniform texture, reducing the density of the composite center, which is conducive to obtaining a good passivation effect in the subsequent process, while also ensuring an excellent light trapping effect, thereby further improving the photoelectric conversion efficiency of the battery.
[0036] In an optional embodiment, the alkaline solution is at least one of a sodium hydroxide solution and a potassium hydroxide solution. In the embodiment of the present application, the type of alkaline solution is optimized, and the alkaline solution etching reconstruction effect is better. The reconstructed velvet surface presents a more uniform texture, reduces the density of the composite center, and is conducive to obtaining a good passivation effect in the subsequent process. At the same time, it can also ensure an excellent light trapping effect, thereby further improving the photoelectric conversion efficiency of the battery.
[0037] In an optional embodiment, the alkaline solution also includes n-butanol; the concentration of the alkali in the alkaline solution is 0.4-0.6 mol / L (for example, 0.4 mol / L, 0.45 mol / L, 0.5 mol / L, 0.55 mol / L, 0.6 mol / L), and the mass concentration of the n-butanol is 5-10% (for example, 5%, 6%, 7%, 8%, 9%, 10%).
[0038] In the embodiment of the present application, the concentration of the alkaline solution is optimized, and then an appropriate amount of n-butanol is added to the alkaline solution, which can promote anisotropic etching of the silicon wafer surface, more deep nanopores are converted into square pits, more nanoscale inverted pyramid structures appear at the bottom, the average pore diameter is increased, the average pore depth is shortened, and the alkaline solution etching reconstruction effect is better. The reconstructed velvet surface presents a more uniform texture, reduces the density of composite centers, and is conducive to obtaining a good passivation effect in the subsequent process. At the same time, it can also ensure an excellent light trapping effect, thereby further improving the photoelectric conversion efficiency of the battery.
[0039] In an optional embodiment, the method of reconstructing the cylindrical nanoporous black silicon texture of the target single crystal silicon wafer by etching with an alkaline solution comprises: placing the target single crystal silicon wafer in the alkaline solution and etching and rebuilding for 20 to 30 seconds (e.g., 20 seconds, 21 seconds, 22 seconds, 23 seconds, 24 seconds, 25 seconds, 26 seconds, 27 seconds, 28 seconds, 29 seconds, 30 seconds); or First, the target single crystal silicon wafer is placed in a first alkaline solution for etching and reconstruction for 10 to 15 seconds (for example, 10 seconds, 11 seconds, 12 seconds, 13 seconds, 14 seconds, and 15 seconds), and then the target single crystal silicon wafer is placed in a second alkaline solution for etching and reconstruction for 10 to 15 seconds (for example, 10 seconds, 11 seconds, 12 seconds, 13 seconds, 14 seconds, and 15 seconds); Wherein, the first alkaline solution is a sodium hydroxide solution, the concentration of sodium hydroxide in the first alkaline solution is 0.4-0.5 mol / L (for example, 0.4 mol / L, 0.41 mol / L, 0.43 mol / L, 0.45 mol / L, 0.47 mol / L, 0.49 mol / L, 0.5 mol / L), and the mass concentration of n-butanol is 5-7% (for example, 5%, 6%, 7%); the second alkaline solution is a potassium hydroxide solution, the concentration of potassium hydroxide in the second alkaline solution is 0.55-0.6 mol / L (for example, 0.55 mol / L, 0.56 mol / L, 0.57 mol / L, 0.58 mol / L, 0.59 mol / L, 0.6 mol / L), and the mass concentration of n-butanol is 9-10% (for example, 9%, 9.2%, 9.4%, 9.6%, 9.8%, 10%).
[0040] In the embodiment of the present application, the alkaline solution etching reconstruction time is optimized, the alkaline solution etching reconstruction is carried out in two stages, and the process parameters of the two stages of alkaline solution etching are optimized, which can promote anisotropic etching of the silicon wafer surface, more deep nanopores are converted into square pits, more nanoscale inverted pyramid structures appear at the bottom, the average pore diameter is increased, the average pore depth is shortened, the alkaline solution etching reconstruction effect is better, the reconstructed velvet surface presents a more uniform texture, and the density of the composite center is reduced, which is conducive to obtaining a good passivation effect in the subsequent process, while also ensuring an excellent light trapping effect, thereby further improving the photoelectric conversion efficiency of the battery.
[0041] The following specific examples further illustrate the present application, but should not be construed as limiting the present application. Without departing from the spirit and substance of the present application, modifications or replacements made to the methods, steps or conditions of the present application are within the scope of the present application.
[0042] Example 1 A method for preparing a TOPCon battery, comprising: (1) Cleaning and texturing: Clean the N-type single crystal silicon wafer to remove the damage on the edge after cutting and the surface impurities. Then place the N-type single crystal silicon wafer in a mixed solution of silver nitrate (AgNO3) / hydrofluoric acid (HF) / hydrogen peroxide (H2O2) and soak it at 25°C for 2 minutes. The concentration of AgNO3 is 0.001 mol / L, the concentration of HF is 8 mol / L, and the concentration of H2O2 is 0.3 mol / L. The prepared b-Si nanotexture structure is as follows: Figure 1 Then, it was washed with deionized water, 0.0008mol / LHNO3 and deionized water for 10 minutes to remove the metal residue, and then etched in 1% HF solution for 30 seconds to remove the silicon oxide layer grown in the cleaning step; finally, the silicon wafer with b-Si nano-texture structure was placed in 0.4mol / L sodium hydroxide solution and reconstructed at room temperature for 20 seconds to obtain a silicon wafer with black silicon velvet, as shown in FIG. Figure 2 shown.
[0043] (2) Boron diffusion: At high temperature, a plasma enhanced chemical vapor deposition (PECVD) system is used to introduce reaction gases such as silane (SiH4), borane (B2H6), and hydrogen (H2). PECVD deposition is used to diffuse and oxidize the boron source on the surface of the black silicon velvet surface to form a PN junction, thereby obtaining a boron-diffused silicon wafer.
[0044] (3) Back side alkaline polishing and cleaning: The back side of the boron-diffused silicon wafer is then subjected to alkaline polishing treatment, and then the silicon wafer is cleaned to obtain an alkaline-polished silicon wafer.
[0045] (4) Deposition: A silicon dioxide (SiO2) tunneling layer is prepared by a plasma-assisted nitrous oxide (N2O) gas oxidation (PANO) method, and reaction gases such as silane (SiH4), phosphine (PH3), hydrogen (H2) and methane (CH4) are introduced to deposit an n-doped amorphous silicon film using PECVD to obtain a silicon wafer with deposited amorphous silicon film. Among them, adding methane (CH4) as a reaction gas can effectively prevent bubbling of the amorphous silicon film, and the deposition effect of the amorphous silicon film is better.
[0046] (5) Phosphorus diffusion: Annealing at 860° C. for 30 min to transform the silicon wafer with the deposited amorphous silicon film into polycrystalline silicon and achieve diffusion of the phosphorus source, thereby obtaining a phosphorus-diffused silicon wafer.
[0047] (6) RCA (Radio Corporation of America Clean) cleaning: The contamination and silicon oxide layer on the surface of the phosphorus-diffused silicon wafer are removed by a standard RCA cleaning procedure to obtain a cleaned cell.
[0048] (7) Passivation: A 5 nm aluminum oxide film is prepared on the cleaned cell by atomic layer deposition (ALD), and annealed for 30 min in a nitrogen atmosphere at 400°C to stimulate hydrogen in the deposition process for hydrogen passivation, thereby forming a passivation layer and obtaining a passivated cell.
[0049] (8) Front and back surface coating: A silicon nitride anti-reflection film is deposited on the passivated cell by PECVD to obtain a cell with an anti-reflection film.
[0050] (9) Screen printing: Electrodes are made on the cell with the anti-reflection film by screen printing technology, and then combined with laser assisted sintering (LECO) to prepare a TOPCon cell.
[0051] Example 2 A method for preparing a TOPCon battery, comprising: (1) Cleaning and texturing: Clean the N-type single crystal silicon wafer to remove the damage on the edge and surface impurities after cutting. Then place the N-type single crystal silicon wafer in a mixed solution of silver nitrate (AgNO3) / hydrofluoric acid (HF) / hydrogen peroxide (H2O2) and soak it at 30°C for 4 minutes. The concentration of AgNO3 is 0.003 mol / L, the concentration of HF is 9 mol / L, and the concentration of H2O2 is 0.6 mol / L. The prepared b-Si nanotexture structure is as follows: Figure 1Then, it was washed with deionized water, 0.0012mol / LHNO3 and deionized water for 10 minutes to remove the metal residue, and then etched in 4% HF solution for 60s to remove the silicon oxide layer grown in the cleaning step; finally, the silicon wafer with b-Si nano-texture structure was placed in 0.6mol / L potassium hydroxide solution and reconstructed at room temperature for 30s to obtain a silicon wafer with black silicon velvet, as shown in FIG. Figure 2 shown.
[0052] (2) Boron diffusion: At high temperature, a plasma enhanced chemical vapor deposition (PECVD) system is used to introduce reaction gases such as silane (SiH4), borane (B2H6), and hydrogen (H2). PECVD deposition is used to diffuse and oxidize the boron source on the surface of the black silicon velvet surface to form a PN junction, thereby obtaining a boron-diffused silicon wafer.
[0053] (3) Back side alkaline polishing and cleaning: The back side of the boron-diffused silicon wafer is then subjected to alkaline polishing treatment, and then the silicon wafer is cleaned to obtain an alkaline-polished silicon wafer.
[0054] (4) Deposition: A silicon dioxide (SiO2) tunneling layer is prepared by a plasma-assisted nitrous oxide (N2O) gas oxidation (PANO) method, and reaction gases such as silane (SiH4), phosphine (PH3), hydrogen (H2) and methane (CH4) are introduced to deposit an n-doped amorphous silicon film using PECVD to obtain a silicon wafer with deposited amorphous silicon film. Among them, adding methane (CH4) as a reaction gas can effectively prevent bubbling of the amorphous silicon film, and the deposition effect of the amorphous silicon film is better.
[0055] (5) Phosphorus diffusion: Annealing at 920° C. for 30 min to transform the silicon wafer with the deposited amorphous silicon film into polycrystalline silicon and achieve diffusion of the phosphorus source, thereby obtaining a phosphorus-diffused silicon wafer.
[0056] (6) RCA (Radio Corporation of America Clean) cleaning: The contamination and silicon oxide layer on the surface of the phosphorus-diffused silicon wafer are removed by a standard RCA cleaning procedure to obtain a cleaned cell.
[0057] (7) Passivation: A 6 nm aluminum oxide film is deposited on the cleaned cell by atomic layer deposition (ALD), and annealed in a nitrogen atmosphere at 450°C for 30 min to excite hydrogen in the deposition process for hydrogen passivation, thereby forming a passivation layer and obtaining a passivated cell.
[0058] (8) Front and back surface coating: A silicon nitride anti-reflection film is deposited on the passivated cell by PECVD to obtain a cell with an anti-reflection film.
[0059] (9) Screen printing: Electrodes are made on the cell with the anti-reflection film by screen printing technology, and then combined with laser assisted sintering (LECO) to prepare a TOPCon cell.
[0060] Example 3 The TOPCon battery of Example 3 was prepared by referring to the preparation method of Example 1, except that: Step (1) in Example 3 is: cleaning the N-type single crystal silicon wafer to remove the damage on the edge after cutting and the surface impurities. Then, the N-type single crystal silicon wafer is placed in a mixed solution of silver nitrate (AgNO3) / hydrofluoric acid (HF) / hydrogen peroxide (H2O2) and immersed for 3 minutes at 27°C, wherein the concentration of AgNO3 is 0.002 mol / L, the concentration of HF is 8.5 mol / L, and the concentration of H2O2 is 0.4 mol / L. The prepared b-Si nano-texture structure is as shown in FIG. Figure 1 Then, the wafer was washed with deionized water, 0.0009 mol / L HNO3 and deionized water for 10 minutes to remove metal residues, and then etched in 2% HF solution for 40 seconds to remove the silicon oxide layer grown in the cleaning step; finally, the silicon wafer with b-Si nano-texture structure was placed in 0.5 mol / L potassium hydroxide solution and reconstructed at room temperature for 25 seconds to obtain a silicon wafer with black silicon velvet.
[0061] Example 4 The TOPCon battery of Example 4 was prepared by referring to the preparation method of Example 3, except that: Step (1) in Example 4 is: cleaning the N-type single crystal silicon wafer to remove the damage on the edge after cutting and the surface impurities. Then, the N-type single crystal silicon wafer is placed in a mixed solution of silver nitrate (AgNO3) / hydrofluoric acid (HF) / hydrogen peroxide (H2O2) and immersed for 3 minutes at 27°C, wherein the concentration of AgNO3 is 0.002 mol / L, the concentration of HF is 8.5 mol / L, and the concentration of H2O2 is 0.4 mol / L. The prepared b-Si nano-texture structure is as shown in FIG. Figure 1 Then, it was washed with deionized water, 0.0009 mol / L HNO3 and deionized water for 10 minutes in sequence to remove metal residues, and then etched in 2 mol / L HF solution for 40 seconds to remove the silicon oxide layer grown in the cleaning step; finally, the silicon wafer with b-Si nano-texture structure was placed in 0.5 mol / L tetramethylammonium hydroxide solution and reconstructed at room temperature for 25 seconds to obtain a silicon wafer with black silicon velvet.
[0062] Example 5 The TOPCon battery of Example 5 was prepared by referring to the preparation method of Example 3, except that: Step (1) in Example 5 is: cleaning the N-type single crystal silicon wafer to remove the damage on the edge after cutting and the surface impurities. Then, the N-type single crystal silicon wafer is placed in a mixed solution of silver nitrate (AgNO3) / hydrofluoric acid (HF) / hydrogen peroxide (H2O2) and immersed for 3 minutes at 27°C, wherein the concentration of AgNO3 is 0.002 mol / L, the concentration of HF is 8.5 mol / L, and the concentration of H2O2 is 0.4 mol / L. The prepared b-Si nano-texture structure is as shown in FIG. Figure 1 Then, the wafer was washed with deionized water, 0.0009 mol / L HNO3 and deionized water for 10 minutes to remove metal residues, and then etched in a 2% HF solution for 40 seconds to remove the silicon oxide layer grown in the washing step; finally, the silicon wafer with the b-Si nano-texture structure was placed in an alkaline solution and reconstructed at room temperature for 25 seconds to obtain a silicon wafer with a black silicon velvet surface; the alkaline solution also included n-butanol; the concentration of the alkali in the alkaline solution was 0.5 mol / L, and the mass concentration of the n-butanol was 5%.
[0063] Example 6 The TOPCon battery of Example 6 was prepared by referring to the preparation method of Example 3, except that: Step (1) in Example 6 is: cleaning the N-type single crystal silicon wafer to remove the damage on the edge after cutting and the surface impurities. Then, the N-type single crystal silicon wafer is placed in a mixed solution of silver nitrate (AgNO3) / hydrofluoric acid (HF) / hydrogen peroxide (H2O2) and immersed for 3 minutes at 27°C, wherein the concentration of AgNO3 is 0.002 mol / L, the concentration of HF is 8.5 mol / L, and the concentration of H2O2 is 0.4 mol / L. The prepared b-Si nano-texture structure is as shown in FIG. Figure 1 Then, the wafer was washed with deionized water, 0.0009 mol / L HNO3 and deionized water for 10 minutes to remove metal residues, and then etched in a 2% HF solution for 40 seconds to remove the silicon oxide layer grown in the washing step; finally, the silicon wafer with the b-Si nano-texture structure was placed in an alkaline solution and reconstructed at room temperature for 25 seconds to obtain a silicon wafer with a black silicon velvet surface; the alkaline solution also included n-butanol; the concentration of the alkali in the alkaline solution was 0.5 mol / L, and the mass concentration of the n-butanol was 10%.
[0064] Example 7 The TOPCon battery of Example 7 was prepared by referring to the preparation method of Example 3, except that: Step (1) in Example 7 is: cleaning the N-type single crystal silicon wafer to remove the damage on the edge after cutting and the surface impurities. Then, the N-type single crystal silicon wafer is placed in a mixed solution of silver nitrate (AgNO3) / hydrofluoric acid (HF) / hydrogen peroxide (H2O2) and immersed for 3 minutes at 27°C, wherein the concentration of AgNO3 is 0.002 mol / L, the concentration of HF is 8.5 mol / L, and the concentration of H2O2 is 0.4 mol / L. The prepared b-Si nano-texture structure is as shown in FIG. Figure 1 As shown. Then, the wafer was washed with deionized water, 0.0009 mol / L HNO3 and deionized water for 10 minutes in sequence to remove metal residues, and then etched in a 2% HF solution for 40 seconds to remove the silicon oxide layer grown in the cleaning step; finally, the silicon wafer with the b-Si nano-texture structure was placed in a first alkaline solution for etching and reconstruction for 10 seconds, and then the silicon wafer with the b-Si nano-texture structure was placed in a second alkaline solution for etching and reconstruction for 10 seconds to obtain a silicon wafer with a black silicon velvet surface; the first alkaline solution was a sodium hydroxide solution, the concentration of sodium hydroxide in the first alkaline solution was 0.4 mol / L, and the mass concentration of n-butanol was 5%; the second alkaline solution was a potassium hydroxide solution, the concentration of potassium hydroxide in the second alkaline solution was 0.55 mol / L, and the mass concentration of n-butanol was 9%.
[0065] Example 8 The TOPCon battery of Example 8 was prepared by referring to the preparation method of Example 3, except that: Step (1) in Example 8 is: cleaning the N-type single crystal silicon wafer to remove the damage on the edge after cutting and the surface impurities. Then, the N-type single crystal silicon wafer is placed in a mixed solution of silver nitrate (AgNO3) / hydrofluoric acid (HF) / hydrogen peroxide (H2O2) and immersed for 3 minutes at 27°C, wherein the concentration of AgNO3 is 0.002 mol / L, the concentration of HF is 8.5 mol / L, and the concentration of H2O2 is 0.4 mol / L. The prepared b-Si nano-texture structure is as shown in FIG. Figure 1 As shown. Then, the wafer was washed with deionized water, 0.0009 mol / L HNO3 and deionized water for 10 minutes in sequence to remove metal residues, and then etched in a 2% HF solution for 40 seconds to remove the silicon oxide layer grown in the cleaning step; finally, the silicon wafer with the b-Si nano-texture structure was placed in a first alkaline solution for etching and reconstruction for 15 seconds, and then the silicon wafer with the b-Si nano-texture structure was placed in a second alkaline solution for etching and reconstruction for 15 seconds to obtain a silicon wafer with a black silicon velvet surface; the first alkaline solution was a sodium hydroxide solution, the concentration of sodium hydroxide in the first alkaline solution was 0.5 mol / L, and the mass concentration of n-butanol was 7%; the second alkaline solution was a potassium hydroxide solution, the concentration of potassium hydroxide in the second alkaline solution was 0.6 mol / L, and the mass concentration of n-butanol was 10%.
[0066] Example 9 The TOPCon battery of Example 9 was prepared according to the preparation method of Example 3, except that: Step (1) in Example 9 is: cleaning the N-type single crystal silicon wafer to remove the damage on the edge after cutting and the surface impurities. Then, the N-type single crystal silicon wafer is placed in a mixed solution of silver nitrate (AgNO3) / hydrofluoric acid (HF) / hydrogen peroxide (H2O2) and immersed for 3 minutes at 27°C, wherein the concentration of AgNO3 is 0.002 mol / L, the concentration of HF is 8.5 mol / L, and the concentration of H2O2 is 0.4 mol / L. The prepared b-Si nano-texture structure is as shown in FIG. Figure 1 As shown. Then, the wafer was washed with deionized water, 0.0009 mol / L HNO3 and deionized water for 10 minutes in sequence to remove metal residues, and then etched in a 2% HF solution for 40 seconds to remove the silicon oxide layer grown in the cleaning step; finally, the silicon wafer with the b-Si nano-texture structure was placed in a first alkaline solution for etching and reconstruction for 15 seconds, and then the silicon wafer with the b-Si nano-texture structure was placed in a second alkaline solution for etching and reconstruction for 15 seconds to obtain a silicon wafer with a black silicon velvet surface; the first alkaline solution was a sodium hydroxide solution, the concentration of sodium hydroxide in the first alkaline solution was 0.5 mol / L, and the mass concentration of n-butanol was 7%; the second alkaline solution was a sodium hydroxide solution, the concentration of sodium hydroxide in the second alkaline solution was 0.6 mol / L, and the mass concentration of n-butanol was 10%.
[0067] Example 10 The TOPCon battery of Example 10 was prepared by referring to the preparation method of Example 3, except that: Step (1) in Example 10 is: cleaning the N-type single crystal silicon wafer to remove the damage on the edge after cutting and the surface impurities. Then, the N-type single crystal silicon wafer is placed in a mixed solution of silver nitrate (AgNO3) / hydrofluoric acid (HF) / hydrogen peroxide (H2O2) and immersed for 3 minutes at 27°C, wherein the concentration of AgNO3 is 0.002 mol / L, the concentration of HF is 8.5 mol / L, and the concentration of H2O2 is 0.4 mol / L. The prepared b-Si nano-texture structure is as shown in FIG. Figure 1As shown. Then, the wafer was washed with deionized water, 0.0009 mol / L HNO3 and deionized water for 10 minutes in sequence to remove metal residues, and then etched in a 2% HF solution for 40 seconds to remove the silicon oxide layer grown in the cleaning step; finally, the silicon wafer with the b-Si nano-texture structure was placed in a first alkaline solution for etching and reconstruction for 15 seconds, and then the silicon wafer with the b-Si nano-texture structure was placed in a second alkaline solution for etching and reconstruction for 15 seconds to obtain a silicon wafer with a black silicon velvet surface; the first alkaline solution was a potassium hydroxide solution, the concentration of potassium hydroxide in the first alkaline solution was 0.5 mol / L, and the mass concentration of n-butanol was 7%; the second alkaline solution was a potassium hydroxide solution, the concentration of potassium hydroxide in the second alkaline solution was 0.6 mol / L, and the mass concentration of n-butanol was 10%.
[0068] Embodiment 11 The TOPCon battery of Example 11 was prepared by referring to the preparation method of Example 3, except that: Step (1) in Example 11 is: cleaning the N-type single crystal silicon wafer to remove the damage on the edge after cutting and the surface impurities. Then, the N-type single crystal silicon wafer is placed in a mixed solution of silver nitrate (AgNO3) / hydrofluoric acid (HF) / hydrogen peroxide (H2O2) and immersed for 3 minutes at 27°C, wherein the concentration of AgNO3 is 0.002 mol / L, the concentration of HF is 8.5 mol / L, and the concentration of H2O2 is 0.4 mol / L. The prepared b-Si nano-texture structure is as shown in FIG. Figure 1 As shown. The silicon wafer with b-Si nanotexture structure was placed in a 0.5 mol / L potassium hydroxide solution and reconstructed at room temperature for 25 seconds; finally, it was washed with deionized water, 0.0009 mol / L HNO3 and deionized water for 10 minutes to remove metal residues, and then etched in a 2% HF solution for 40 seconds to remove the silicon oxide layer grown in the cleaning step, and a silicon wafer with black silicon velvet was obtained.
[0069] Example 12 The TOPCon battery of Example 12 was prepared by referring to the preparation method of Example 3, except that: Step (1) in Example 12 is: cleaning the N-type single crystal silicon wafer to remove the damage on the edge after cutting and the surface impurities. Then, the N-type single crystal silicon wafer is placed in a mixed solution of silver nitrate (AgNO3) / hydrofluoric acid (HF) / hydrogen peroxide (H2O2) and immersed for 3 minutes at 27°C, wherein the concentration of AgNO3 is 0.0007 mol / L, the concentration of HF is 7 mol / L, and the concentration of H2O2 is 0.2 mol / L. The prepared b-Si nano-texture structure is as shown in FIG. Figure 1Then, the wafer was washed with deionized water, 0.0009 mol / L HNO3 and deionized water for 10 minutes to remove metal residues, and then etched in 2% HF solution for 40 seconds to remove the silicon oxide layer grown in the cleaning step; finally, the silicon wafer with b-Si nano-texture structure was placed in 0.5 mol / L potassium hydroxide solution and reconstructed at room temperature for 25 seconds to obtain a silicon wafer with black silicon velvet.
[0070] Example 13 The TOPCon battery of Example 13 was prepared by referring to the preparation method of Example 3, except that: Step (1) in Example 13 is: cleaning the N-type single crystal silicon wafer to remove the damage on the edge after cutting and the surface impurities. Then, the N-type single crystal silicon wafer is placed in a mixed solution of silver nitrate (AgNO3) / hydrofluoric acid (HF) / hydrogen peroxide (H2O2) and immersed for 3 minutes at 27°C, wherein the concentration of AgNO3 is 0.005 mol / L, the concentration of HF is 9.5 mol / L, and the concentration of H2O2 is 0.7 mol / L. The prepared b-Si nano-texture structure is as shown in FIG. Figure 1 Then, the wafer was washed with deionized water, 0.0009 mol / L HNO3 and deionized water for 10 minutes to remove metal residues, and then etched in 2% HF solution for 40 seconds to remove the silicon oxide layer grown in the cleaning step; finally, the silicon wafer with b-Si nano-texture structure was placed in 0.5 mol / L potassium hydroxide solution and reconstructed at room temperature for 25 seconds to obtain a silicon wafer with black silicon velvet.
[0071] Comparative Example 1 The TOPCon battery of Comparative Example 1 was prepared by referring to the preparation method of Example 3, except that: Step (1) in Comparative Example 1 is: using plasma dry etching to etch the surface of an N-type single crystal silicon wafer to prepare a cylindrical nanoporous black silicon velvet surface, wherein the pore size of the cylindrical nanoporous black silicon velvet surface is 40 to 80 nm, and the pore depth of the cylindrical nanoporous black silicon velvet surface is 150 to 250 nm, thereby obtaining a silicon wafer having a black silicon velvet surface.
[0072] Comparative Example 2 The TOPCon battery of Comparative Example 2 was prepared by referring to the preparation method of Example 3, except that: Step (1) in Comparative Example 2 is: using plasma dry etching to etch the surface of an N-type single crystal silicon wafer to prepare a cylindrical nanoporous black silicon velvet surface, wherein the pore size of the cylindrical nanoporous black silicon velvet surface is 50 to 70 nm, and the pore depth of the cylindrical nanoporous black silicon velvet surface is 180 to 220 nm, thereby obtaining a silicon wafer having a black silicon velvet surface.
[0073] Comparative Example 3 The TOPCon battery of Comparative Example 3 was prepared by referring to the preparation method of Example 3, except that: The step (1) in comparative example 3 is: taking an N-type single crystal silicon wafer, and etching the pyramid velvet surface by wet etching to obtain a silicon wafer with a velvet surface; Step (2) in Comparative Example 3 is: at high temperature, using a plasma enhanced chemical vapor deposition (PECVD) system to introduce reaction gases silane (SiH4), borane (B2H6), and hydrogen (H2), and using PECVD deposition to diffuse and oxidize the boron source on the textured surface to form a PN junction, thereby obtaining a boron-diffused silicon wafer.
[0074] The TOPCon cells prepared in the above examples and comparative examples were subjected to photoelectric tests, and the test results are shown in Table 1 below.
[0075] Table 1 (Using Comparative Example 3 as a reference, the performance improvement comparison data of Examples 1-13 and Comparative Examples 1-2 are obtained.)
[0076] In Table 1 above, taking Example 1 as an example, the Eta (%) of Example 1 = 0.10%; specifically, when the Eta (%) of the battery in Comparative Example 3 is X%, and the Eta (%) of the battery in Example 1 is Y%, it satisfies: Y%-X%=0.10%. The FF (%) of Example 1 = 0.12%; specifically, when the FF (%) of the battery in Comparative Example 3 is A%, and the FF (%) of the battery in Example 1 is B%, it satisfies: B%-A%=0.12%.
[0077] The Isc (mA) of Example 1=22mA, which specifically means that when the Isc (mA) of the battery in Comparative Example 3 is XmA and the Isc (mA) of the battery in Example 1 is YmA, the following condition is satisfied: YX=22mA.
[0078] Referring to the detection data of the above-mentioned Examples 1-13 and Comparative Examples 1-2, it can be seen that a black silicon (b-Si) nano-suede structure is first prepared based on a metal-assisted chemical etching method (MACE) to form a densely and evenly arranged deep cylindrical nanoporous black silicon suede; then an alkaline solution is used to etch and reconstruct the surface suede, and the shallow surface of the densely arranged deep cylindrical nanopores on the surface of the black silicon (b-Si) nano-suede structure is etched. Due to the anisotropic etching, the deep nanopores are converted into square pits, and more nanoscale inverted pyramid structures appear at the bottom, the average pore diameter is increased, and the average pore depth is shortened. The reconstructed suede surface presents a uniform texture, and the surface / volume ratio is greatly reduced, thereby reducing the density of the composite center, which is conducive to obtaining a good passivation effect in the subsequent process, while also ensuring an excellent light trapping effect, and improving the photoelectric conversion efficiency and open circuit voltage of solar cells.
[0079] Referring to the detection data of the above-mentioned Examples 3 and 4, it can be seen that by optimizing the type of alkaline solution, the alkaline solution etching reconstruction effect is better, the reconstructed velvet surface presents a more uniform texture, and the density of the composite center is reduced, which is conducive to obtaining a good passivation effect in the subsequent process. At the same time, it can also ensure an excellent light trapping effect, thereby further improving the photoelectric conversion efficiency of the battery.
[0080] Referring to the detection data of the above-mentioned Example 3 and Examples 5-6, it can be known that optimizing the concentration of the alkaline solution and adding an appropriate amount of n-butanol to the alkaline solution can promote anisotropic etching of the silicon wafer surface, more deep nanopores are converted into square pits, more nanoscale inverted pyramid structures appear at the bottom, the average pore diameter is increased, the average pore depth is shortened, the alkaline solution etching reconstruction effect is better, the reconstructed velvet surface presents a more uniform texture, and the density of the composite center is reduced, which is conducive to obtaining a good passivation effect in the subsequent process, while also ensuring an excellent light trapping effect, thereby further improving the photoelectric conversion efficiency of the battery.
[0081] Referring to the detection data of the above-mentioned Examples 3, 7-8, and 9-10, it can be seen that optimizing the alkaline solution etching reconstruction time, performing the alkaline solution etching reconstruction in two stages, and optimizing the various process parameters of the two stages of alkaline solution etching can promote anisotropic etching of the silicon wafer surface, more deep nanopores are converted into square pits, more nanoscale inverted pyramid structures appear at the bottom, the average pore diameter is increased, the average pore depth is shortened, the alkaline solution etching reconstruction effect is better, the reconstructed velvet surface presents a more uniform texture, and the composite center density is reduced, which is conducive to obtaining a good passivation effect in the subsequent process, while also ensuring an excellent light trapping effect, thereby further improving the photoelectric conversion efficiency of the battery.
[0082] Referring to the detection data of the above-mentioned Example 3 and Example 11, it can be seen that after metal-assisted chemical etching, the target single crystal silicon wafer is subjected to impurity removal treatment before alkaline solution etching reconstruction, and the alkaline solution etching reconstruction effect is better. The reconstructed velvet surface presents a more uniform texture, which reduces the density of the composite center, and is conducive to obtaining a good passivation effect in the subsequent process. At the same time, it can also ensure an excellent light trapping effect, thereby further improving the photoelectric conversion efficiency of the battery.
[0083] With reference to the detection data of the above-mentioned Example 3 and Examples 12-13, it can be known that optimizing the composition ratio of the black silicon texturing liquid can improve the microstructure of the velvet surface, so as to obtain a black silicon velvet surface with densely and uniformly arranged cylindrical nanopores. On the one hand, it can increase the light trapping effect, which is beneficial to light capture and reduces light reflection loss, thereby improving the photoelectric conversion efficiency of the battery; on the other hand, controlling the microstructure of the cylindrical nanoporous black silicon velvet surface is beneficial to the subsequent alkaline solution etching reconstruction step, and the alkaline solution etching reconstruction effect is better. The reconstructed velvet surface presents a more uniform texture, which reduces the density of the composite centers, and is conducive to obtaining a good passivation effect in the subsequent process. At the same time, it can also ensure an excellent light trapping effect, thereby further improving the photoelectric conversion efficiency of the battery.
[0084] In addition, in the above-mentioned Examples 5-10, a rough, densely arranged deep cylindrical nanoporous b-Si velvet is first obtained based on the metal-assisted chemical etching method (MACE), with an average pore size distribution of 40-80nm and an average pore depth distribution of 150-250nm. Subsequently, the surface velvet is reconstructed by etching with an alkaline solution; in Examples 5-6 and Examples 9-10, after etching and reconstruction with an alkaline solution, the average pore size is expanded to 180-220nm, and the average pore depth is slightly shortened to 100-140nm. In Examples 7-8, after etching and reconstruction with an alkaline solution, the average pore size is expanded to 190-230nm, and the average pore depth is slightly shortened to 90-120nm, and the passivation effect is more significantly improved. It can also be seen from this that optimizing the alkaline solution etching reconstruction time, dividing the alkaline solution etching reconstruction into two stages, and optimizing the various process parameters of the two stages of alkaline solution etching can promote anisotropic etching of the silicon wafer surface, more deep nanopores are converted into square pits, more nanoscale inverted pyramid structures appear at the bottom, the average pore diameter is increased, the average pore depth is shortened, the alkaline solution etching reconstruction effect is better, the reconstructed velvet surface presents a more uniform texture, and the density of the composite center is reduced, which is conducive to obtaining a good passivation effect in the subsequent process. At the same time, it can also ensure an excellent light trapping effect, thereby further improving the photoelectric conversion efficiency of the battery.
[0085] In summary, the present application first prepares a black silicon (b-Si) nano-suede structure based on a metal-assisted chemical etching method (MACE) to form a densely and evenly arranged deep cylindrical nanoporous black silicon suede; then an alkaline solution is used to etch and reconstruct the surface suede, and the shallow surface of the densely arranged deep cylindrical nanopores on the surface of the black silicon (b-Si) nano-suede structure is etched. Due to the anisotropic etching, the deep nanopores are converted into square pits, and more nanoscale inverted pyramid structures appear at the bottom, the average pore diameter increases, and the average pore depth shortens. The reconstructed suede surface presents a uniform texture, and the surface / volume ratio is greatly reduced, thereby reducing the density of the recombination center, which is conducive to obtaining a good passivation effect in the subsequent process, while also ensuring an excellent light trapping effect, and improving the photoelectric conversion efficiency and open circuit voltage of solar cells.
[0086] The embodiment of the present application can provide a TOPCon solar cell (not shown), including a single crystal silicon wafer prepared by the above method; the TOPCon solar cell is prepared by the following operations: on the single crystal silicon wafer, a PN junction, a silicon dioxide tunneling layer, an n-doped amorphous silicon film, an aluminum oxide film, a silicon nitride anti-reflection film and a metal electrode are sequentially prepared.
[0087] The embodiment of the present application can provide a photovoltaic system, including the TOPCon solar cell in any of the above embodiments. The advantages of the above TOPCon solar cell are also possessed by the photovoltaic system, which will not be repeated here. The above photovoltaic system has a wide range of applications, not only limited to photovoltaic power stations, such as ground power stations, rooftop power stations and water power stations, but also includes various equipment and devices that use solar energy to generate electricity, such as user solar power supplies, solar street lights, solar cars and solar buildings. Of course, it can be understood that the application scenarios of the photovoltaic system are not limited to this, that is to say, the photovoltaic system can be used in all fields where solar energy is required for power generation. Taking the photovoltaic power generation system network as an example, the photovoltaic system may include a photovoltaic array, a junction box and an inverter. The photovoltaic array may be an array combination of multiple photovoltaic components. For example, multiple photovoltaic components can form multiple photovoltaic arrays. The photovoltaic array is connected to the junction box. The junction box can converge the current generated by the photovoltaic array. The converged current flows through the inverter and is converted into the alternating current required by the mains power grid and then connected to the mains network to realize solar power supply.
[0088] It should be noted that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application. The orientation words "inside" and "outside" refer to the inside and outside relative to the outline of each component itself. For example, if the device in the accompanying drawings is inverted, the device described as "above other devices or structures" or "above other devices or structures" will be positioned as "below other devices or structures" or "below other devices or structures". Therefore, the exemplary term "above..." can include both "above..." and "below..." orientations. The device can also be positioned in other different ways (rotated 90 degrees or in other orientations), and the spatial relative descriptions used here are interpreted accordingly.
[0089] It should also be noted that "one embodiment", "another embodiment", "embodiment", etc. mentioned in this application refer to the specific features, structures or characteristics described in conjunction with the embodiment included in at least one embodiment generally described in this application. The same expression appearing in multiple places in the specification does not necessarily refer to the same embodiment. Further, when describing a specific feature, structure or characteristic in conjunction with any embodiment, it is claimed that the realization of such feature, structure or characteristic in conjunction with other embodiments also falls within the scope of this application.
[0090] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0091] It should also be noted that the above are only preferred embodiments of the present application, and the patent protection scope of the present application is not limited thereto. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A method for preparing a single crystal black silicon texture, characterized in that: include: Putting a single crystal silicon wafer into a black silicon texturing solution, and performing metal-assisted chemical etching on the single crystal silicon wafer to form a cylindrical nanoporous black silicon texturing surface, thereby obtaining a target single crystal silicon wafer; Reconstructing the cylindrical nanoporous black silicon texture of the target single crystal silicon wafer by etching with an alkaline solution to form an inverted pyramid texture structure; Among them, the average pore diameter of the cylindrical nanoporous black silicon velvet surface is smaller than the average tower base length of the inverted pyramid velvet surface structure, and the average pore depth of the cylindrical nanoporous black silicon velvet surface is greater than the average tower height of the inverted pyramid velvet surface structure.
2. The method according to claim 1, characterized in that The pore diameter of the cylindrical nanoporous black silicon velvet surface is 40 to 80 nm, and the pore depth of the cylindrical nanoporous black silicon velvet surface is 150 to 250 nm; and / or The length of the tower base of the inverted pyramid-shaped velvet structure is 180-220 nm, and the tower height of the inverted pyramid-shaped velvet structure is 100-140 nm.
3. The method according to claim 1, characterized in that The black silicon texturing solution includes silver nitrate, hydrogen fluoride, hydrogen peroxide and water; wherein the concentration of the silver nitrate is 0.001-0.003 mol / L, the concentration of the hydrogen fluoride is 8-9 mol / L, and the concentration of the hydrogen peroxide is 0.3-0.6 mol / L.
4. The method according to claim 3, characterized in that During the metal-assisted chemical etching of the single crystal silicon wafer, the temperature is controlled at 25-30° C. and the time is controlled at 2-4 minutes.
5. The method according to claim 1, characterized in that Before the target single crystal silicon wafer is subjected to alkaline solution etching reconstruction, the method further comprises: sequentially using deionized water, a nitric acid solution having a nitric acid concentration of 0.0008 to 0.0012 mol / L, and deionized water to clean the target single crystal silicon wafer; and / or The target single crystal silicon wafer is placed in a hydrofluoric acid solution having a mass concentration of 1 to 4% of hydrogen fluoride for etching for 30 to 60 seconds.
6. The method according to any one of claims 1 to 5, characterized in that The alkaline solution is at least one of a sodium hydroxide solution and a potassium hydroxide solution.
7. The method according to claim 6, characterized in that The alkaline solution also includes n-butanol; the concentration of the alkali in the alkaline solution is 0.4-0.6 mol / L, and the mass concentration of the n-butanol is 5-10%.
8. The method according to claim 7, characterized in that The method of reconstructing the cylindrical nanoporous black silicon texture of the target single crystal silicon wafer by etching with an alkaline solution comprises: Placing the target single crystal silicon wafer into the alkaline solution for etching and reconstruction for 20 to 30 seconds; or Firstly, the target single crystal silicon wafer is placed in a first alkaline solution for etching and reconstruction for 10 to 15 seconds, and then the target single crystal silicon wafer is placed in a second alkaline solution for etching and reconstruction for 10 to 15 seconds; Wherein, the first alkaline solution is a sodium hydroxide solution, the concentration of sodium hydroxide in the first alkaline solution is 0.4-0.5 mol / L, and the mass concentration of n-butanol is 5-7%; the second alkaline solution is a potassium hydroxide solution, the concentration of potassium hydroxide in the second alkaline solution is 0.55-0.6 mol / L, and the mass concentration of n-butanol is 9-10%.
9. A TOPCon solar cell, characterized in that: A single crystal silicon wafer prepared by the method according to any one of claims 1 to 8; The TOPCon solar cell is prepared by the following operations: on the single crystal silicon wafer, a PN junction, a silicon dioxide tunneling layer, an n-doped amorphous silicon film, an aluminum oxide film, a silicon nitride anti-reflection film and a metal electrode are sequentially prepared.
10. A photovoltaic system, characterized in that: Comprising the TOPCon solar cell as claimed in claim 9.
Citation Information
Cited By
Solar cell and preparation method thereof, laminated cell and photovoltaic module
CN120857701A